A Study On Women Entrepreneurs Running Small Enterprises In And Around Chandigarh - Upadhyay, Archan (Gyan Management Journal, 2020)
Entrepreneurship is the only key that provides more job providers than seekers. The role of this concept  is manifold in the increased economic activity within the country. Women entrepreneurs are leading  their way to success but have to pass various hurdles in their path to success. This study was conducted  on fifty women entrepreneurs through Judgemental sampling in Tricity. The enterprises selected for  study wereHandicrafts, Designer clothes, Bakery Business, Organic Dairy Business, Chocolate Business,  Designer Jewellery Business boutiques etc. Female Entrepreneurs faced financial problems, problems  in managing personal and work life etc. The study suggests that the problems can be solved if the  budding female entrepreneurs get support from all fronts be it societal, professional, government and  family.
Keywords: Women entrepreneurs; social achievement; retail business; motivators; seed capital; MSME